2021
DOI: 10.1016/j.arthro.2021.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Causes of Failure After Arthroscopic Rotator Cuff Repair

Abstract: Causes of failure after arthroscopic rotator cuff repair include patient factors, tear factors, and surgical factors. Failure may occur at the sutureetendon interface, the boneetendon interface, or the boneeanchor interface. Low bone mineral density (BMD) in the greater tuberosity has been reported as a prognostic factor for recurrent tears following rotator cuff repair, and although most studies suggest the tendon-to-suture interface as the "weakest link," patients with low BMD may have lower suture anchor pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…39,43,45 The healing interface between different tissues is also susceptible to suture cutting and chronic inflammation. 4,11,14,38 In this context, the impaired healing between the patch and rotator cuff tendons or the greater tuberosity makes these 2 interfaces vulnerable to failure. 6,[28][29][30]47,48 Furthermore, the patch materials currently used have structural properties inferior to rotator cuff tendons and thus may not guarantee initial mechanical strength, reliable postoperative patch substance remodeling, or interface healing with the rotator cuff tendon or the humeral head, particularly in resisting localized high-tensile force in the rotator cuff force chain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39,43,45 The healing interface between different tissues is also susceptible to suture cutting and chronic inflammation. 4,11,14,38 In this context, the impaired healing between the patch and rotator cuff tendons or the greater tuberosity makes these 2 interfaces vulnerable to failure. 6,[28][29][30]47,48 Furthermore, the patch materials currently used have structural properties inferior to rotator cuff tendons and thus may not guarantee initial mechanical strength, reliable postoperative patch substance remodeling, or interface healing with the rotator cuff tendon or the humeral head, particularly in resisting localized high-tensile force in the rotator cuff force chain.…”
Section: Discussionmentioning
confidence: 99%
“…8,23,35 In MRCTs, the chronic and retracted rotator cuff tendons with fatty degeneration result in a weak structural attachment for grafting, particularly with simple suturing methods that may produce more localized, undue cutting and chronic inflammation at the suture-soft tissue interface. 2,38,39,43,45 Mori et al 30 used a suture mattress technique to affix the FL autograft patch in bridging reconstruction. They reported that on magnetic resonance imaging, 80% of the nonintact repaired shoulders (27/34 shoulders) showed a full-thickness high-intensity area (indicating retear) at the medial bridging construct of the native rotator cuff and cuff-to-graft interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,10,18,36 In contrast, the pulling force in the bone tunnel by whipstitch sutures was parallel to the tensile force in the intratunnel portions of the Plug-Pat, which decreased the tension at the graft-suture interface. 23,24,38 Furthermore, these specially designed bone fixation constructs in the Plug-Pat resulted in superior contact characteristics when compared with the conventional Rect-Pat. The increased graft-bone refreshed contact area has been reported to optimize the pressurized contact distributions at time zero and have less propensity for gap formation, which may also contribute to the superior initial fixation strength in the Plug-Pat.…”
Section: Discussionmentioning
confidence: 99%
“…14 The factors that bring about the high failure rate of RCR have multiple aspects; 14,21 namely, patient factors, tear factors, and surgical factors. 22,24 Among them, surgical factors have a critical effect on tendon-bone healing after RCR. 27 Surgical factors can be subdivided into the repair technique, suture anchors, preparation of the greater tuberosity, and structural augmentation.…”
mentioning
confidence: 99%